2021
DOI: 10.3390/v14010024
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Human Papillomavirus Genotypes, According to the Human Immunodeficiency Virus Status in a Cohort of Women from Maputo, Mozambique

Abstract: Background: Human papillomavirus (HPV) infection is now a well-established cause of cervical cancer and other anogenital cancers. An association between human immunodeficiency virus (HIV) infection and higher HPV incidence and prevalence are commonly reported. This study was conducted to demonstrate HPV prevalence, genotypes and its characteristics, according to the HIV status in women from Maputo in Mozambique. Methods: A total of 233 participants with ages ranging from fourteen to forty-five were included. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Contrarily, information from LMIC sites is very scant [ 21 ], but existing data suggest that PSCC may have a distinctive epidemiological background, with most tumors arising via an HPV-associated pathway [ 22 ]. A high prevalence of HPV infections has been reported in many LMIC, with Mozambique showing an incidence as high as 63% [ 23 ]. As HPV-associated tumors tend to affect younger individuals, patients from Spain were almost two decades older in average than patients from Mozambique, a pattern also observed in vulvar squamous cell carcinomas [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, information from LMIC sites is very scant [ 21 ], but existing data suggest that PSCC may have a distinctive epidemiological background, with most tumors arising via an HPV-associated pathway [ 22 ]. A high prevalence of HPV infections has been reported in many LMIC, with Mozambique showing an incidence as high as 63% [ 23 ]. As HPV-associated tumors tend to affect younger individuals, patients from Spain were almost two decades older in average than patients from Mozambique, a pattern also observed in vulvar squamous cell carcinomas [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Our results show that, although the current WHO 2020 classification separates VSCC into HPVassociated and HPV-independent tumors and recommends the use of HPV testing and/or p16 IHC for the proper classification, this requirement should probably be considered unnecessary in many sub-Saharan countries, where the number of HPV-independent tumors is likely to be extremely low, and the resources and laboratory capacities are, in general, particularly limited. 23 In addition to the high prevalence of HPV infection, the high prevalence of HIV infection in Mozambique 24 has been proposed as the most likely explanation for the increase in the incidence in cancer of the uterine cervix observed in Mozambique and several sub-Saharan countries. 22 According to the UNAIDS Global Report, the prevalence of HIV in Mozambique was as high as 45% in women aged 28 to 47 in a community-based study in a rural district of Maputo province, 25 with a high number of patients not receiving antiretroviral treatment and presenting with AIDS.…”
Section: P53 Ihc Resultsmentioning
confidence: 99%
“…In addition to the high prevalence of HPV infection, the high prevalence of HIV infection in Mozambique 24 has been proposed as the most likely explanation for the increase in the incidence in cancer of the uterine cervix observed in Mozambique and several sub‐Saharan countries 22 . According to the UNAIDS Global Report, the prevalence of HIV in Mozambique was as high as 45% in women aged 28 to 47 in a community‐based study in a rural district of Maputo province, 25 with a high number of patients not receiving antiretroviral treatment and presenting with AIDS 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Omar and colleagues reported a prevalence of infection with any HPV genotype in Mozambique of 63.6%, the majority of whom were infected with genotypes 16 or 18 (Omar et al, 2017); however, Omar et al (2017) studied women aged 18-21, much younger than our sample. Maueia et al (2022), although with a relatively small sample, aged between 18 and 45 years old, reported in Maputo, Mozambique, an overall HPV prevalence of 63%, which is significantly higher among HIV-infected women (McDonald et al, 2014). South Africa reported a higher HPV prevalence among HIV-infected women (52.4%) than among HIV-uninfected women (20.8%) (McDonald et al, 2014), while, Castle et al (2020) Botswana reported hrHPV prevalences of 40.4% (95% CI, 36.3-44.5%) for women living with HIV and 25.2% (95% CI, 21.2-29.4%) for HIV uninfected women.…”
Section: Discussionmentioning
confidence: 99%
“…(2017) studied women aged 18–21, much younger than our sample. Maueia et al . (2022), although with a relatively small sample, aged between 18 and 45 years old, reported in Maputo, Mozambique, an overall HPV prevalence of 63%, which is significantly higher among HIV-infected women (McDonald et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%